REVIEW OF MICRO-MILLING TECHNOLOGY - TIAN Lu; HAN XuZhao; GAO Feng; HAN Chuang (Jixie qiangdu)
Micro-milling can fabricate 3 D free-form surface and complex components and has a promising prospect. However, due to sharp decreases of the tool scale and machining parameters, micro-milling process shows remarkable differences from traditional milling, thus researchers conduct broad studies on micro-milling technology recent years. The process of micro-milling is complicated and involves many aspects, the domestic and overseas researches in micro-milling are summed up in this paper, the development of minimum chip thickness, cutting force, surface roughness, tool wear, and other aspects of researches are summarized. The development trend of micro-milling and the application prospect are discussed.